The Structure of Evaluative Anthroponymic Semantics of Siberian Tatars - Ravil Gilfanov, Farida Gilfanova, Luisa Chamsutdinova, (Opción, 2019)
The article analyzes the anthroponymic semantics of adjectives, that is, evaluativity of naming, which allowed the authors to reconstruct value-evaluative relations between a subject and an object via qualitative comparative research method. As a result, the object of evaluative relationships varied with the religiousness level, starting with the fact that a name was implicated with the religious rituals of the pre-Islamic period, then a name began to include the epithets of the Most High and, finally, a name became merely a symbol. In conclusion, the cultural and historical development of society and ethnic groups directly reflects in linguistic processes